Impact of Online Education in Making Global Learning Accessible - Omotosho, Tunde Victor (Àgídìgbo: ABUAD Journal of the Humanities, 2015)
In the midst of the rising integration of online education or e-learning into academic courses, there is strong need for realistic course of action and recommendations to make the improvement possible and release of pedagogically efficient e-learning environments. The objective of this paper is to make clear the educational advantages that take place while supplementing learning by means of online device. This article also suggested that the use of technology in our educational system in teaching and learning will allow educators to plan for courses and programs that will facilitate learning by distant students in the same way as campus based students as well as for each individual student's learning ability, and it offered some background that are essential to advance the objective of making education and learning accessible to all without necessarily disrupting their other daily activities as the learning is done at their own appointed time, place and pace. It concluded with considerations of how the staff responsibility will, of necessity, revolutionize as a consequence of these advances in our understanding of using technology to improve learning outcomes. This is intended at answering basic questions on the subject of the nature as well as scope of online education, taking into consideration the state of e-learning in Nigeria today.